2016
DOI: 10.5505/actamedica.2016.07108
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for a Hospital Ethics Committee at the Hacettepe University Hospitals, Turkey: A Mixed Method Study

Abstract: Introduction: Hospital Ethics Committees (HECs) were established to solve the ethical dilemmas experienced by health personnel in clinics. However, HECs also provide training on ethics, and develop ethics guidelines and institutional policies. HECs first appeared in the USA in the 1960s and had become widespread in Europe by the 1990s. In Turkey, the introduction of HECs is relatively recent and the number of committees is limited. The aim of this study was to identify the need for a HEC at the Hacettepe Unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
(13 reference statements)
1
5
0
Order By: Relevance
“…Most medical oncologists participating in our study reported a requirement of clinical ethical consultation for guidance when faced with ethical dilemmas. This result was expected considering the limited and ineffective hospital ethics committees and consultancy services in Turkey . Our study demonstrates that young medical oncologists have a greater requirement for such services, suggesting an increase in ethical awareness as in the last decade, ethical subjects have become more common in medical training curriculum.…”
Section: Discussionsupporting
confidence: 58%
“…Most medical oncologists participating in our study reported a requirement of clinical ethical consultation for guidance when faced with ethical dilemmas. This result was expected considering the limited and ineffective hospital ethics committees and consultancy services in Turkey . Our study demonstrates that young medical oncologists have a greater requirement for such services, suggesting an increase in ethical awareness as in the last decade, ethical subjects have become more common in medical training curriculum.…”
Section: Discussionsupporting
confidence: 58%
“…Clinical colleagues from a hospital Trust in the North West of England help to facilitate clinical ethics workshops and grade clinical ethics coursework at their local medical school where medical students learn, apply, and critique clinical ethics frameworks to their own and others’ cases. Clinical colleagues appreciate the opportunity to be involved in such activities as they acknowledge that they had not received such in-depth ethical training when they attended medical school compared to current medical students as others have noted elsewhere (Demir and Büken 2016 ). Senior clinicians also feel the weight of expectations upon them to be able to support junior colleagues when facing ethical and legal challenges, yet are often uncertain how to approach and resolve their own as well as others’ ethical dilemmas.…”
Section: Recognising a Need For Clinical Ethics Support In One Nhs Trmentioning
confidence: 99%
“…Despite the on-going vocal support for clinical ethics, on the ground there has been little financial investment or regulatory support underpinning its presence in the UK, which is disturbing when contemplating the state of ethics training available to healthcare practitioners. It is well known that current senior doctors have not received such in-depth ethical training as deemed essential by the General Medical Council for today’s medical students [ 9 ]. Research has also highlighted the lack of ethical and legal training available once doctors qualify [ 15 , 23 ].…”
Section: The State Of Clinical Ethics In the Ukmentioning
confidence: 99%